Video head impulse test in stroke: a review of published studies - Jaganathan, Niranjana; Mohamed, Mohd Hazmi; Md Pauzi, Ahmad Luqman; Mahayidin, Hasni; Hanapai, Ahmad Firdaus; Wan Sulaiman, Wan Aliaa; Basri, Hamidon; Inche Mat, Liyana (Frontiers in Neurology, 2024)
Accurate and timely diagnosis of posterior circulation stroke in patients with acute dizziness is a challenge that can lead to misdiagnosis and significant harm. The present review sought to identify and describe published research on the clinical application of vHIT in posterior circulation stroke. vHIT, a portable device, has gained prominence in evaluating peripheral vestibular disorders and offers potential applications in diagnosing neurological disorders, particularly posterior circulation stroke. Several studies have shown that vHIT can differentiate between stroke and vestibular neuritis based on VOR gain values, with high sensitivity and specificity. The manuscript also discusses vHIT’s performance in differentiating between types of posterior circulation stroke, such as PICA, AICA, and SCA strokes. While vHIT has demonstrated promise, the review emphasizes the need for further research to validate its use as a tool to rule out stroke in acute dizziness patients in the emergency department. In conclusion, the manuscript underscores the potential of vHIT as a valuable addition to the diagnostic arsenal for acute dizziness, particularly in the context of posterior circulation stroke. It calls for further research and wider adoption of vHIT in clinical settings to improve patient care and reduce unnecessary costs associated with misdiagnoses.